Successful Treatment of Iatrogenic Multicentric Castleman's Disease Arising Due to Recrudescence of HHV‐8 in a Liver Transplant Patient - Speicher, D. J.; Sehu, M. M.; Mollee, P.; Shen, L.; Johnson, N. W.; Faoagali, J. L. (American journal of transplantation, 2014)
We describe the case of a 59‐year‐old HIV‐negative male who developed multicentric Castleman's disease (MCD) 1 year postliver transplantation due to recrudescence of a pretransplant human herpesvirus‐8 (HHV‐8) infection. He presented with fevers, dry cough, weight loss and drenching night sweats. Routine investigations were all unremarkable. Computerized axial tomography (CT) scans showed splenomegaly and intra‐abdominal lymphadenopathy, confirmed by positron emission tomography. Cervical lymph node biopsies were consistent with MCD. The presence of HHV‐8 was confirmed on immunohistochemistry. Peripheral blood HHV‐8 quantitative polymerase chain reaction (qPCR) monitoring showed a threefold decrease in viremia in the first week of treatment with ganciclovir but had little impact on clinical symptoms. Reducing immunosuppression and switching to rituximab resolved clinical symptoms and produced a negative HHV‐8 qPCR result. Retrospective molecular testing of sera collected pre‐ and immediately posttransplantation confirmed preexisting HHV‐8 in the host. This is the first reported case of an HIV‐negative postliver transplant patient developing MCD that manifested as posttransplant lymphoproliferative disorder due to recrudescence of HHV‐8. We propose (1) the introduction of the term iatrogenic Castleman's disease (CD) for this and similar cases, (2) rituximab should be considered as a treatment option for CD and (3) consideration be given to a change to the World Health Organization classification of CD to incorporate such cases. The authors report the development of iatrogenic Castleman's disease in an HIV‐negative male 1 year post‐liver transplantation who was treated successfully by reducing immunosuppression and administering rituximab.